2021
DOI: 10.1155/2021/6613439
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Effect of Lenvatinib Combined with Alisertib in Hepatocellular Carcinoma by Targeting the DNA Damage Pathway

Abstract: Background and Aim. Although a strong antitumor effect of lenvatinib has been noted for patients with unresectable hepatocellular carcinoma (HCC), its efficacy requires improvement. It is imperative to seek therapeutic strategies that combine Lenvatinib with other anticancer agents. In this study, we investigated the anticancer effect of combining lenvatinib with alisertib, aurora A kinase (AURKA) target drug, against HCC in vitro and in vivo. Methods. Immunohistochemical staining, sequencing, and genetic anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…New drugs -lenvatinib in the frontline and regorafenib, cabozantinib, and ramucirumab in the second line -have also been demonstrated to improve clinical outcomes, but the median overall survival of these treatments still remains ~1-year, therapeutic breakthroughs are still needed. A recent study showed that alisertiblenvatinib combination contributes to the anti-tumor activity in HCC cells and xenograft tumors model 44 .…”
Section: Discussionmentioning
confidence: 99%
“…New drugs -lenvatinib in the frontline and regorafenib, cabozantinib, and ramucirumab in the second line -have also been demonstrated to improve clinical outcomes, but the median overall survival of these treatments still remains ~1-year, therapeutic breakthroughs are still needed. A recent study showed that alisertiblenvatinib combination contributes to the anti-tumor activity in HCC cells and xenograft tumors model 44 .…”
Section: Discussionmentioning
confidence: 99%
“…New drugs—lenvatinib in the frontline and regorafenib, cabozantinib, and ramucirumab in the second line—have also been demonstrated to improve clinical outcomes, but the median overall survival of these treatments still remains ~1-year, therapeutic breakthroughs are still needed. A recent study showed that alisertib-lenvatinib combination contributes to the anti-tumor activity in HCC cells and xenograft tumors model [ 44 ]. The role of AURKA inhibitor in the treatment of HCC still needs more studies, including exploring more combined treatment methods and screening potential benefit patient groups, which will speed up the clinical promotion of alisertib in the treatment of HCC, and also provide more treatment options for advanced HCC.…”
Section: Discussionmentioning
confidence: 99%
“…81 Another study demonstrated that AURKA was significantly upregulated in 22 primary liver cancer tissues of HCC patients (77.3%, 17/22) (Table 2). 82 Given its involvement in cancer, high levels of AURKA have been linked to clinical aggressiveness, poor outcomes, unfavourable prognoses, therapeutic resistance, and increased early recurrence in HCC patients. 80,84 The patients showing high AURKA expression (n = 52) had significantly shorter overall survival (OS) and diseasefree survival rates compared to the patients with low AURKA expression (n = 86) (Table 2).…”
Section: Expression Pattern Of Aurka In Hccmentioning
confidence: 99%
“…137,138 Alisertib increased the cytotoxic effects and anti-metastatic activity of lenvatinib in Hep3B (p53-deletion) and HepG2 (wild type), which may suggest that this combinatorial treatment may be effective regardless of p53 mutational status. 82 Similarly, the simultaneous inhibi- AFP, and des-gamma-carboxy-prothrombin (DCP). 145 However, the significant heterogeneity in HCC underscores the limitations of the available systems in comprehensively stratifying the patients.…”
Section: Targeting Aurka For Liver Cancer Therapymentioning
confidence: 99%
See 1 more Smart Citation